Perancangan Antarmuka Sistem Informasi Pelaporan Paud Berbasis Web dengan pendekatan metode User Centered Design - Aji Sutiawan; Dwi Rosa Indah (LPPM STIKOM Tunas Bangsa, 2023)
In 2022/2023, the number of PAUD/TK and PNF schools in the Musi Banyuasin area is recorded at 1,262 schools, the increasing number of schools causes constraints in the conventional reporting process. As it is often late, reports take up a lot of space, the data in the report is also often not in accordance with applicable technical instructions so it must be returned for correction, as well as a long journey. The purpose of this study is to design an ECCE reporting information system interface that is useful to assist the ECCE reporting process at the Musi Banyuasin Education and Culture Office using the User-Cenetered Design method. The stages in User-Ceneterd Design consist of context analysis, requirement determination, design and evaluation. Based on research that has been conducted by conducting usability testing by applying the System Usability Scale, the final score is obtained, namely: 86.33 with category A or